TWIN PREGNANCY WITH FETUS ACARDIAC: CONSERVATIVE MANAGEMENT. A CASE REPORT - Arias, Jorge (2015)
We present a twin gestation with one acardic fetus, extremely rare, with an incidence of 1/35 000 gestations and almost 100% mortality for the acardic fetus and a 50% for the normal fetus. The existence of an acardiac fetus generates an overcharge in the normal fetus because of both arteries and arteriolae and veins and venules anatomoses, causing extra work to the healthy heart in order to maintain both circulations and multiple anomalies in the receptor fetus; the hemodynamic overcharge in the giver fetus can originate cardiac failure, hidrops, polyhydramnios and preterm labor. In this case we chose a conservative attitude with a combination of medical treatment (digitalics) with serial amniocentesis.